The causes of adhesive direct dental restorations failures - Irina-Maria Gheorghiu; Paula Perlea; Alexandru Andrei Iliescu; Mihai Sebastian Onu; Sanziana Scarlatescu (Amaltea Medical Publishing House, 2023)
The modern dental caries adhesive direct restoration requires a working protocol that includes stages and techniques that must be strictly followed to ensure the correct morphological and functional reconstruction, as well as an increased longevity of the restoration and implicitly of the respective tooth in the oral cavity. Failures in achieving these goals are represented by the occurrence of recurrent caries, secondary or residual caries, coronary fractures, leading to pulpal and periodontal complications. They can be due to both incorrect therapeutic maneuvers and other causes, for which the dentist is not responsible, such as manufacturing defects of dental materials that are not visible during inspection or the patient's attitude towards oral hygiene.